Risk Factors and Clinical Characteristics of Neonatal Acute Respiratory Distress Syndrome Caused by Early Onset Sepsis - You, Ting; Zhou, Yan-Rong; Liu, Xiao-Chen; Li, Lu-Quan (Frontiers in Pediatrics, 2022)
Purpose To identify risk factors associated with the development of acute respiratory distress syndrome (ARDS) in infants with early onset sepsis (EOS) and to describe the clinical features. Methods A retrospective study was conducted at the Children’s Hospital of Chongqing Medical University between January 2000 and October 2020. The infants were divided into ARDS and non-ARDS groups. Clinical characteristics and risk factors were compared between the two groups. Results Two hundred fifty infants (58 with ARDS) were included. Smaller gestational age, lower birth weight (LBW), lower serum albumin level, a higher rate of preterm birth, premature rupture of membranes, antenatal steroid exposure, and lower Apgar score were associated with an increased development of ARDS by univariate analysis (P < 0.05). LBW (β = −0.001, P = 0.000, OR: 0.999, 95% CI: 0.998–0.999) and low serum albumin levels (β = −0.063, P = 0.022, OR: 0.939, 95% CI: 0.889–0.991) were identified as independent risk factors for the development of ARDS by logistic regression analysis. A higher frequency of complications, including persistent pulmonary hypertension, intraventricular hemorrhage, pulmonary hemorrhage, septic shock, and bronchopulmonary dysplasia, was found in the ARDS group (P < 0.05). The rate of mortality was higher for those in the ARDS group than for those in the non-ARDS group (46.6% vs. 15.6%, χ2 = 24.205, P = 0.000). Conclusion Acute respiratory distress syndrome (ARDS) in EOS could lead to a higher frequency of complications and mortality. The risk factors for the development of ARDS were LBW and low serum albumin levels.